2008
DOI: 10.1007/s00417-008-0990-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of clonidine on VEGF expression in human retinal pigment epithelial cells (ARPE-19)

Abstract: The effect of clonidine on the expression of VEGF may be via suppression of the p38MAPK and MEK1/2 signal transduction pathways activated with IL-1beta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The concentrations of these substances positively correlated with the anticancer activity demonstrated by the strains. Interestingly, several reports have proven that oleic acid, oleanolic acid, yohimbine and cytidine possess anticancer activity by the suppressing tumour metastasis [ 35 38 ]. Furthermore, natural products containing these compounds have been reported to inhibit the expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of these substances positively correlated with the anticancer activity demonstrated by the strains. Interestingly, several reports have proven that oleic acid, oleanolic acid, yohimbine and cytidine possess anticancer activity by the suppressing tumour metastasis [ 35 38 ]. Furthermore, natural products containing these compounds have been reported to inhibit the expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…28 It was previously reported that ARPE19 cells could produce inflammatory cytokines under the stimulation of TNFa or IL-1b, through ERK1/2 and JNK pathways, 54,55 which indicate possible methods to control inflammatory retinal diseases by inhibiting these inflammatory factors and pathways. 55,56 Moreover, previous study indicated that these cytokines were related to Th1 differentiation. 36 We found that neutralization of IL-1b inhibited A2E-laden RPE cell function on Th1-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), which is likely caused by both the CRVO-induced tissue hypoxia and retinal inflammation. It has been shown that inflammatory factors such as IL-1 ␤ cause an upregulation of Vegfa in retinal cells [17,18] . The decrease in the expression of Vegfa after 3 days of CRVO might be related to the upregulation of Pedf observed for this time period ( fig.…”
Section: Discussionmentioning
confidence: 99%